Epiphany Storytelling as a Means of Reinforcing and Embedding Transformational Therapeutic Change - Fletcher, Joan (European Journal for Qualitative Research in Psychotherapy, 2008)
Recently the mental health field has seen a groundswell of interest in user perspectives as a crucial element of enlightened research, training and service enhancement. Despite a stated commitment to user empowerment and collaboration, due to a range of ethical concerns there has been relatively little research into the phenomenological, micro-momentary experience of those on the receiving end of therapy. We have failed to mine the rich experience of clients, particularly members of social minority groups. This paper aims to address this gap by shedding light on the intricacies of the therapeutic relationship; the alchemy between a particular professional and client that can lead to profound and transformational change. The paper highlights the somatic-affective-cognitive-spiritual dimensions to such encounters or “turning points”, their autobiographical significance and how these dimensions can usefully be encapsulated and explored within the concept of “epiphany”.